A Literature Review on Big Data Analytics (International Journal of Innovative Research in Computer Science & Technology, 2021)
Huge volumes of data have been available  to policymakers in the digital world. Big data is a term to  collections that are not always huge, but also varied and fast  changing, rendering standard tools and procedures  inadequate. Due to the quick creation of such data,  techniques to organize and retrieve value and knowledge  from these sets must be explored and given. Additionally,  choice should be able to obtain relevant information from  that wide and continuously changing collection of data,  which encompasses everything from ordinary activities to  customer communication and social data. Analytics, and that  is the deployment of advanced analytics methodologies to  enormous volumes of data, may deliver such value. It article  looks at some of the numerous analytics concepts and  methods that may be utilized utilizing massive data, or the  prospects that data analytics might provide in many decision  domains.
Keywords: Analytics; Big Data; Data Mining; Decision Making